Brain maturation in the first 3 months of life, measured by electroencephalogram: A comparison between preterm and term-born infants. Issue 10 (October 2019) - Guyer, Caroline; Werner, Helene; Wehrle, Flavia; Bölsterli, Bigna Katrin; Hagmann, Cornelia; Jenni, Oskar G.; Huber, Reto
Highlights: Topographical analysis of sleep EEG shows qualitative differences in preterm infants in early life. A central activation at term age predicts being more mature at 3 months of age. In future, automated tools using topographical power distribution may identify infants at risk. Abstract: Objective: Preterm infants are at risk for altered brain maturation resulting in neurodevelopmental impairments. Topographical analysis of high-density electroencephalogram during sleep matches underlying brain maturation. Using such an EEG mapping approach could identify preterm infants at risk early in life. Methods: 20 preterm (gestational age < 32 weeks) and 20 term-born infants (gestational age > 37 weeks) were recorded by 18-channel daytime sleep-EEG at term age (GA 40 weeks for preterm and 2–3 days after birth for term infants) and 3 months (corrected age for preterm infants). Results: Preterm infant's power spectrum at term age is immature, leveling off with term infants at 3 months of age. Topographical distribution of maximal power density however, reveals qualitative differences between the groups until 3 months of age. Preterm infants exhibit more temporal than central activation at term age and more occipital than central activation at 3 months of age. Moreover, being less mature at term age predicts being less mature at 3 months of age. Conclusion: Topographical analysis of sleep EEG reveals changes in brain maturation between term and preterm infants early in life. Significance: In future, automated analysis tools using topographical power distribution could help identify preterm infants at risk early in life.